Governing Groundwater Irrigation in Bangladesh: Reviewing the Past and Looking Ahead for the Future - Sarkar, Anindita; Mukherji, Aditi; Mainuddin, M. (2024)
Groundwater governance in intensively irrigated agricultural regions of global south is receiving increased attention due to its growing complexities in responding to multifaceted challenges, of rapidly growing populations, demand for food production, increasing pressure on land and water resources, escalating energy use and cost of irrigation and uncertain climate futures. This paper therefore aims to enrich current understanding of irrigation policies by drawing insights from Bangladesh. It traces the historical evolution of groundwater irrigation development in Bangladesh’s agriculture in five phases since 1960’s. Each of these phases are analysed to show how policies impact groundwater irrigation systems and what can we learn from these experiences. Extension of groundwater irrigation is determined by government’s decisions to influence both public and private investments on groundwater technologies and new innovative cost-effective technologies in groundwater irrigation systems. The paper argues that shifts in governance decisions on irrigation polices can impact agrarian change. The study finds that although the shifts in governance approaches have cumulatively improved the food security of Bangladesh, they have not been framed to provide direction for its sustainable use in the long run. At present the country is trying to find solutions to balance optimum utilization of groundwater amidst challenges of adopting to new pumping technologies and renewable energy sources to reduce irrigation cost in one hand and addressing the escalating apprehension of groundwater depletion and decline in food production on the other.